Analysis Of The Implementation Of Financial Reportsbased On Sak Of The Palm Oil Farmers Group Of Kud Sriwijaya Village Sp 3 Pelakat Tinggi Regency Of Musi Banyuasin South Sumatera - Wahyuningsih, Tri; Herlin, Herlin; Hidayah, Nenden Restu (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
Implementation of PSAK No. 201 Regarding the presentation of financial statements is a complete financial statement consisting of a statement of financial position, income statement, statement of changes in equity, cash flow statement, and notes to the financial statements. The purpose of implementing PSAK No. 201 financial in decision making is to provide detailed information and provide third party trust.The purpose of this study is to determine the analysis of the application of financial reports based on SAK of the KUD Sriwijaya oil palm farmer group, SP 3 Pelakat Tinggi Village, Musi Banyuasin Regency, South Sumatra Province which has been in accordance with Accounting standards. The method used in this study is a Descriptive Qualitative comparative approach. Data collection techniques used by the author are by conducting observations, interviews and documentation.The results of the study indicate that the analysis of the application of accounting standards for oil palm farmer groups in SP 3 Pelakat Tinggi Village, Musi Banyuasin Regency, South Sumatra Province from the results of this study indicate that the financial reports that have been applied/presented by the oil palm farmer groups in SP 3 Pelakat Tinggi Village, Musi Banyuasin Regency, South Sumatra Province are said to be inappropriate because only one component of the financial report, namely the financial position report, namely the balance sheet and profit and loss statement, the statement of changes in equity, and the statement of notes to the financial statements are not presented or applied, this is said to be inappropriate because of the lack of 4 components that are not presented with the accounting standards PSAK No. 201.